Polllnation Biology, Seed Setting and Fruit Setting in Madhuca indica (Sapotaceae) - Kuruvilla, P. K. (Indian Forester, 1989)
The different aspects affecting seed setting and fruit setting in Madhuca indica are investigated. The mode of pollination is anemophillic. The seed setting rate is low even in hand pollinations due to (1) lack of distribution of the pollen tubes in all the styla Canals, (2) competition for stored resources between early fertilized ovules and late fertilized ovules. The fruit development occurs simultaneously alongwith vegetative bud sprouting. The vegetative sink dominates, hereby resulting in the abscission of the developing fruits.